Sosialisasi Learning management System melalui Platform Quizziz - Elyza Martiarini; Nurhayati Hasbi (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
This community service aims to train the instructors of the Nuansa Jaya Education Skills Institute (LKP) to conduct socialization with the theme of learning management based on the 4.0 revolutionary era learning management for teachers or teaching staff at LKP Nuansa Jaya located in Kota Bambu Selatan, Palmerah, West Jakarta. One of the platforms included in Learning Management System based learning is Quizizz. The Quizizz platform is an example of using technology in learning that uses today's approach to the millennial generation. This web tool helps the role of teaching staff or teachers to facilitate students in learning, taking test scores, alternative media, and ice breaking during learning activities. As quoted on the gatraguru.net page, here are the steps to use the Quizizz platform as a Learning Management System based learning. Overall, this socialization not only provides knowledge about the use of the Quizziz platform, but also in general in terms of preparing interesting and interactive learning media, especially in dealing with learning in the pandemic era.